KEDUDUKAN KUASA MENJUAL ATAS DASAR SURAT KETERANGAN NOTARIS TENTANG PEMBAYARAN LUNAS DALAM PEMBUATAN AKTA JUAL BELI BALIK NAMA - , SH, Sumardi (Acta Comitas : Jurnal Hukum Kenotariatan, 2016)
Agreement Cordage Deed of Sale-Buy and Sell Attorney basically represent evidence appliance showing tied of the parties in an agreement about goods and price / object as sales contract. Meanwhile by normatif, problem to existence of sell attorney which was utilized in registration of land right switchover did not be arrangement in Government Regulation No. 24 Year 1997 about Land Registry. The blankness of the Norm had caused the happening of solving of registration of land right switchover which different each other between PPAT according to knowledge had and its bravery strive invention of law. Based of the situation, hence problem of this research is how to exsitance Notary letter statement which is power with sell as base making of sale act buy to return the name of made by and/or before PPAT and do attorney Sell following Notary letter statement can be conceived as an absolute power and sale-buy to name return can be made by appliance to registration of land right switchover at Land Office. Based on the blankness of norm in the Government Regulation No. 24 Year 1997 for the existence of Agreement Cordage Deed of Sale-Buy and Sell Attorney , hence this research was be classified into normative legal research with appproached by conceptual and statute appproach. The legal materials of this research were based on primary, secondary and tertiary legal materials. The legal materials was be descripted henceforth to be interpreted, systematization, analysed, evaluated and also given argument to get conclusion of the problems. Result of the research indicate that dimiciling Notary statement letter with attorney sell was as aid agreement and act underhand as a mean to protect buyer position as well as to help the Notary/PPAT work in making sale-buy act along with registration of land right switchover becoming sales object. Meanwhile, have the sell attorney following Notary  statement letter non as absolute attorney, but as a help deed from antecedent agreement (aid agreement) functioning and have a purpose to draw up, to affirming, strengthening, arranging, altering or finishing its sales contractual terms before notary/PPAT come up with registration of land right switchover becoming sales object.
Keywords: Exsistence, Attorney sell, Deed, Notary, statement letter, keel